Positive practices of the catering industry of the Russian Federation in the COVID-19 pandemic - E. V. Burdenko; G. V. Korolev (Вестник университета)
The novelty of the study is the generalization and analysis of statistical data obtained as a result of various sociological and scientific studies on the impact of the COV-ID-19 pandemic on the activities of the public catering sector in the Russian Federation. The authors carried out a study of positive practices that allowed the industry enterprises to continue to operate in self-isolation and improve financial results with the easing of restrictions. Among them are simplified terms for renting premises; sale of finished products by delivery to the direct consumer or pickup; non-standard formats of catering enterprises; restoration of demand for catering; application of new technologies in the process of cooking; introduction of vending machines in the catering industry; cooperation of catering enterprises with the tourism business.